Family Medicine and Oral Health Screening: Roles of Health Administration, Nurses, Dentists, and Laboratory Technicians - Mumdooh Raja G Alenazy; Waad Hejji Alanazi; Eshteyq Treef Alrwaili; Anwar Mukammi Kulaib Alruwaili; Abdulaziz Khalifa Ali Alanazi; Manal Mohammed L Alenezi; Alrawaili, Abdalmagid Gharip B; Hilal Khalaf Alenezi; Alhazmi, Reem Faleh S; Mohammed Muhaydi Alhazml; et al. (International Journal of Computational and Experimental Science and Engineering, 2024)
The persistent historical divide between medical and dental care represents a significant flaw in healthcare delivery, with detrimental consequences for patient outcomes and systemic efficiency. Health administrators are identified as the crucial architects of system integration, responsible for policy development, workflow redesign, financial incentivization, and fostering a culture of collaboration. Nurses and primary care providers are positioned as the frontline implementers, conducting risk assessments, visual screenings, patient education, and initiating coordinated referrals. Dentists and dental hygienists serve as essential collaborative partners, providing definitive diagnosis and treatment while engaging in the co-management of patients with shared systemic conditions. Laboratory technicians underpin this model with objective data, offering diagnostic clarity through routine tests (e.g., HbA1c), microbiological analysis, and histopathological evaluation, thereby strengthening the evidence-based management of the oral-systemic link. Interdisciplinary collaboration leads to earlier disease detection, improved chronic disease management, enhanced patient outcomes, and a more efficient use of healthcare resources.